Approach to residual dizziness after successfully treated benign paroxysmal positional vertigo: effect of a polyphenol compound supplementation - Casani AP; Navari E; Albera R; Agus G; Asprella Libonati G; Chiarella G; Lombardo N; Marcelli V; Ralli G; Scotto di Santillo L; Teggi R; Viola P; et al. (Dove Medical Press, 2019)
Augusto Pietro Casani,1 Elena Navari,1 Roberto Albera,2 Giuseppe Agus,3 Giacinto Asprella Libonati,4 Giuseppe Chiarella,5 Nicola Lombardo,6 Vincenzo Marcelli,7 Giovanni Ralli,8 Leonardo Scotto di Santillo,9 Roberto Teggi,10 Pasquale Viola,5 Luigi Califano111Department of Medical and Surgical Pathology, Otorhinolaryngology Section, Pisa University, Pisa, Italy; 2Division of Otorhinolaryngology, Department of Surgical Sciences, University of Turin School of Medicine, Turin, Italy; 3Otorhinolaryngology, Private Practice, Cagliari, Italy; 4Ear, Nose and Throat Department, Unit of Audiology, Vestibology and Phoniatry, Madonna delle Grazie Hospital, Matera, Italy; 5Department of Experimental and Clinical Medicine, Unit of Audiology and Phoniatrics, Magna Græcia University, Catanzaro, Italy; 6Otorhinolaryngology Section, Mater Domini University, Catanzaro, Italy; 7Department of Neuroscience, Vestibular and Audiology Unit, University of Naples “Federico II”, Naples, Italy; 8Department of Sense Organs, Sapienza University of Rome, Rome, Italy; 9Vestibology and Vestibular Rehabilitation Unit, Antero Micone Hospital, Genoa, Italy; 10Ear, Nose and Throat Department, San Raffaele Scientific Hospital, Milan, Italy; 11Audiovestibology Unit, G. Rummo Hospital, Benevento, ItalyPurpose: To assess if a polyphenol compound supplementation (Vertigoval®) could improve residual dizziness earlier after benign paroxysmal positional vertigo (BPPV) and relieve patients from this disabling symptomatology.Methods: In this prospective, multicentric study, 127 patients were randomized in the treatment group (TG), who received a 60-day supplementation, while 131 patients were randomized in the control group (CG), who did not receive any medication. The dizziness handicap inventory (DHI) score, static posturography, and the visual analog scale (VAS) for both dizziness (D-VAS) and nausea/vomit (N/V-VAS) were used as measures of outcome at baseline and after 30 and 60 days. Patients were asked about efficacy and tolerance to the treatment. Side effects were examined.Results: A statistically significant greater decrease was established in the TG for DHI, D-VAS, and N/V-VAS compared to the CG. On the other hand, static posturography did not show statistical differences between the two groups, though a better clinical improvement after 60-day supplementation was shown in the TG in comparison to the CG. We counted mild side effects in only 2 patients. Most patients reported an excellent or good efficacy and tolerance to the treatment.Conclusion: Residual dizziness is a frequent condition of unknown origin that manifests as persistent disabling imbalance after successful repositioning maneuvers for BPPV. The decreasing postural control can affect the quality of life, contributing to falling and psychological problems. The supplementation with the polyphenol compound used in our study is safe, manageable, and appeared to be able to reduce subjective symptoms and improve instability earlier, decreasing the risk of potential complications.Keywords: residual dizziness, benign, paroxysmal positional vertigo, BPPV, Vertigoval®